Strength and shrinkage of incinerated waste paper sludge ash based geopolymer concrete incorporating recycle concrete aggregate / Khairulniza Ahmad Anuar - Ahmad Anuar, Khairulniza (2015)
Concrete is widely used as construction material. However, the production material of concrete which is cement (OPC) and natural aggregate (NA) become are major concern. Waste paper sludge ash (WPSA) is a by-product and problematic waste of paper industries in Malaysia. WPSA is found having a potential to replace OPC as a concrete binder. Geopolymer concrete technology is seen as one of the best option to reduce the amount of CO² emitted in OPC production in order to satisfy construction material needs. The use of Recycle Concrete Aggregate (RCA) may help to reduce the effects of the construction and demolition (C&D) activities by reusing waste materials and preventing NA from being harvested. Somehow the utilization of by-product material such as WPSA with RCA in geopolymer concrete was very limited. The main reasons to use RCA in this geopolymer concrete is to make construction more "green" and environmental friendly. Therefore, the WPSA based geopolymer concrete incorporating RCA are been conducted. The main objective of this present study is to determine the compressive strength and shrinkage performance of WPSA based geopolymer concrete incorporating RCA. In the present study, WPSA and the combination of sodium hydroxide (NaOH) and sodium silicate (Na2SiOs) were used as a binder. Fifteen (15) series of specimens comprising three (3) different molarities of NaOH which are 8M, 12M and 14M and different percentages of RCA which are 0%, 25%, 50%, 75% and 100% were adopted. There are 270 cube specimens size 100mm x 100mm x 100mm and 45 prism specimens size 300mm x 75mm x 75mm were prepared. The tests were conducted after aging the specimen at 1, 3, 7, 14, 28, 56 and 90 days cured in ambient temperature. The mineralogical composition and microstructural of the geopolymer were also determined by using X-ray Florescence (XRF), Scanning electron microscopy (SEM) and elemental analysis using Energy Dispersive X-Ray Spectroscopy (EDX). Experimental results show the highest compressive strength was obtained with the use of 12M NaOH which is 6.788 N/mm². However the shrinkage level of the geopolymer is low with range 3.5 x 10⁻⁵ to 7.0 x 10⁻⁵ for all series. SEM of the WPSA based geopolymer concrete indicated that the presence of NaOH and Na₂Si0₃ produced low porosity of geopolymer due to low geopolymerization rate and heterogeneous matrix with a high content of unreacted element.